EASY ACCESS TO PUBLIC TRANSPORTATION FOR SUSTAINABLE SITE DEVELOPMENT, ACASE STUDY OF UNISULLA KALIGAWE SEMARANG - Muhammad Ismail Hasan; Anityas Dian Susanti; Chely Novia Bramiana (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2019)
Abstract: Global warming issue generates some sustainable-oriented actions aiming at protecting and improving environment quality. Air pollution caused by vehicles is one of the causes of global warming. Sustainability can be started in academic phase, such as campus environment, landscape, and buildings. This paper aims at explaining the sustainable development in Sultan Agung Islamic University (UNISSULA) and especially in its sustainable site development. Method used for this paper is qualitative case study that is suitable to answers questions about how and why. Case study requires a collection of site’s data as much as possible before being analyzed based on relevant theories. The result of this paper suggested the applications of sustainable site development in a campus ground especially with an easy access public transportation for Islamic campus and with Islamic values within.Keyword: Campus Ground, Site Development, Sustainable Architecture Abstrak: Isu pemanasan global menyebabkan beberapa aksi keberlanjutan yang pada dasarnya bertujuan untuk melindungi dan meningkatkan kualitas lingkungan. Polusi udara yang disebabkan oleh kendaraan bermotor adalah merupakan salah satu penyebab pemanasan global. Keberlanjutan dapat dimulai dari tingkat akademisi, seperti lingkungan kampus, lansekap, dan bangunan-bangunannya. Paper ini bertujuan untuk menjelaskan pembangunan keberlanjutan di Universitas Islam Sultan Agung (UNISSULA) dan khususnya pada bagian pembanguan site yang berkelanjutan. Metode yang digunakan untuk paper ini adalah kualitatif studi kasus yang dinilai cocok untuk menjawab pertanyaan mengenai bagaimana dan mengapa. Studi kasus membutuhkan pengumpulan data dari site sebanyak mungkin sebelum dianalisa berdasarkan teori yang berhubungan. Hasil dari paper ini dapat menjelaskan pembangunan site yang berkelanjutan terutama pada kemudahan mengakses transportasi umum pada kampus Islam dan dilengkapi dengan nilai-nilai Islam yang terkandung di dalamnya.Kata Kunci: Kampus, Site Berkelanjutan, Arsitektur Berkelanjutan